Design, Synthesis, and Biological Evaluation of New Analogs of Aurein 1.2 Containing Non-Proteinogenic Amino Acids - Nora Angelova; Ivan Iliev; Veronica Nemska; Tatyana Dzimbova; Nelly Georgieva; Dancho Danalev; Emilia Naydenova (Molecules)
Extensive use of classical antibiotics has led to the growing emergence of many resistant strains of pathogenic bacteria. To combat this challenge, researchers have turned to the antimicrobial peptides (AMPs). Aurein 1.2 (GLFDIIKKIAESF-NH2) was demonstrated to have broad spectrum bi-functionality against bacterial and cancer cells. The Solid Phase Peptide Synthesis (Fmoc-strategy) was used for the synthesis of new analogs of aurein 1.2. The purity of all compounds was monitored by HPLC, and their structures were proven using mass spectrometry. Cytotoxicity and antiproliferative effects were studied using 3T3 NRU and MTT tests, respectively. The antibacterial activity was estimated against Gram-positive and Gram-negative bacteria using broth microdilution method in concentrations from 0 to 320 µg/mL to determine the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC). The antiproliferative activity test shows that the peptide analog EH [Orn]8 has the highest activity (IC50 = 44 ± 38 μM) for the three cell lines studied (MCF-12F, MCF-7, and MDA-MB-231). The same compound exhibited good antimicrobial activity. The obtained results reveal that replacement of Lys with non-proteinogenic amino acids can increase both the potency and activity spectra of natural template peptides, making them suitable candidates for new drug development.